Application of Autochthonous Lactobacillus Strains as Biopreservatives to Control Fungal Spoilage in Caciotta Cheese. (16th July 2018) - Cosentino, Sofia; Viale, Silvia; Deplano, Maura; Fadda, Maria Elisabetta; Pisano, Maria Barbara
Abstract : Fungal spoilage is one of the main causes of economic losses worldwide in the food industry. In the last years, consumer's demands for preservative-free processed foods have increased as a result of growing awareness about the health hazards associated with chemicals. Lactic acid bacteria have been extensively studied for their antibacterial and antifungal potential in order to be used as biopreservatives. The first objective of this study was to investigate in vitro the antifungal activity of autochthonous Lactobacillus strains against moulds commonly associated with cheese spoilage. Then, the Lactobacillus strains with the highest inhibitory effect and broadest spectrum were tested in single or mixed cultures against Penicillium chrysogenum ATCC 9179 and Aspergillus flavus ATCC 46283 on miniature Caciotta cheese produced at laboratory scale to evaluate in situ their ability to prevent mould growth and to determine their impact on cheese organoleptic properties and starter culture activity. The growth of the starter lactococcal population exhibited similar trend and values during ripening, suggesting that the addition of lactobacilli did not influence its growth and survival. Inhibition of P. chrysogenum inoculated in the milk was determined in cheeses produced with single or mixed Lactobacillus adjuncts as compared to cheeses without adjunct. The mixed adjunct cultures resulted in more effective, significantly reducing mould counts of more than 2 log units at the end of ripening. The application of the adjunct cultures resulted in a delay in mycelial growth of P. chrysogenum and A. flavus inoculated on the cheese surface as well. Finally, we found no significant differences among samples for the sensory parameters evaluated that received similar ratings. Our results indicate that the selected Lactobacillus strains may have a potential effect in controlling mould contamination on cheeses. Further studies are currently being carried out to identify the molecules responsible for the antifungal activity.